Vitamin D Deficiency in Breast Cancer Patients and its Association with Histopathological Tumor Characteristics (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of vitamin D deficiency in women with breast carcinoma and to determine the association of vitamin D levels with histopathological tumor characteristics.Study Design: Observational Study.Place and Duration of Study: This study was conducted at the Oncology Department, Nishtar Medical College / Hospital Multan from April 2016 to October 2016.Materials and Methods: Ninety female patients with diagnosis of breast cancer on histopathology reporting were selected. A specialized Proforma was used to get information about their personal life e.g. marital status, menopause history, age, BMI, educational status and daily life style. Vitamin D levels were measured in all females. Information regarding tumor grade, stage, type of carcinoma and hormonal receptor status was extracted from pathology, histology and hematology reports of patients.Results: The mean age of study participants was 46.64+10.64 Years. All of the participants were married. 48 (53.3%) patients were in post-menopausal period. 74 (82.2%) were urban residents. Mean vitamin D levels in study participants were 17.78+14.66 ng/ml. There were 56 (62.2%) patients with deficient vitamin D levels, 18 (20.0%) with sub-optimal and 16 (17.8%) patients with optimal vitamin D levels. We did not found any strong association of vitamin D levels with tumor grades, stage and expression of tumor PR and HER-2 receptors. However in our study, tumor ER receptors expression was significantly high in patients in deficient and optimal vitamin D levels as compared to the patients with suboptimal vitamin D levels.Conclusion: There is high prevalence of vitamin D deficiency in breast cancer patients. We did not found any association of vitamin D levels with tumor characteristics.